Electrolyte Balance in Broiler Growing Diets - Borges, Sebastiao Aparecido; da Silva, Ana Vitoria Fischer; Moura, Ana Silvia Alves Meira Tavares; Maiorka, Alex; Ostrensky, Andre (International Journal of Poultry Science, 2004)
Two experiments were carried out using 1,120 chicks to evaluate the electrolyte balance (EB = Na+K-Cl) in growing (21-42 days) broiler diets. The feed, based on corn and soybean meal with 20.0% CP and 3,200 kcal ME/kg, was offered ad libitum. In experiment I, K level was fixed, but Na and Cl levels varied among the four treatments, which included five replications of 40 birds each. In experiment II, increasing levels of Na and K were used, with a total of four treatments and four replications of 20 birds. In both experiments, the EB treatments were 40; 140; 240 and 340 mEq/kg of feed. EB showed a quadratic effect on weight gain and feed to gain ratio when the electrolyte ratio was increased only by the supplementation of Na. Feed intake was maximum for 264 mEq/kg, when Na level was increased in the diet, and 213 mEq/kg, when K and Na levels were concurrently increased in the diet, indicating that there is a limit over which feed intake is depressed as a function of excessive Na and/or K. The ideal EB, obtained by the manipulation of Na and Cl levels, was between 202 and 235 mEq/kg.